High-strength steel plate with excellent bendability and formability and manufacturing method thereof
Patent Information
- Application Number
- JP2023535638
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-14
- Filing Date
- 2021-11-22
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2041-11-22
Smart Images

Figure 0007640701000004 
Figure 0007640701000005 
Figure 0007640701000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a steel suitable as a material for automobiles, and more particularly to a high-strength steel sheet excellent in bendability and formability, and a method for producing the same. [Background technology]
[0002] Recently, in the automotive industry, environmental regulations regarding CO2 emissions and energy usage regulations have led to a demand for the use of high-strength steel to improve fuel efficiency and durability.
[0003] In particular, as regulations on the impact stability of automobiles become more stringent, high-strength steel, which has excellent strength, is being used as a material for structural members such as members, seat rails, and pillars to improve the impact resistance of the vehicle body.
[0004] These automobile parts have complex shapes depending on the design and are mainly manufactured by forming using press dies, so they require high strength as well as a high level of formability.
[0005] While the higher the strength of steel, the better it is at absorbing impact energy, there is a problem that, in general, as strength increases, the elongation decreases, which reduces formability. Moreover, if the yield strength is too high, the flow of material from the die during forming decreases, resulting in poor formability and an increase in manufacturing costs.
[0006] In addition, because automobile parts have many forming areas that expand after holes are drilled, bendability is required for smooth forming, but high-strength steel has low bendability and there is a problem that defects such as cracks occur during forming. If bendability is poor like this, cracks may occur in the forming parts of the parts during a car collision, and the parts may easily break, threatening the safety of passengers.
[0007] On the other hand, representative high-strength steels used as automotive materials include dual phase steel (DP steel), transformation induced plasticity steel (TRIP steel), complex phase steel (CP steel), and ferrite bainite steel (FB steel).
[0008] DP steel, which is an ultra-high tensile steel, has a low yield ratio of about 0.5 to 0.6, making it easy to process, and has the advantage of having the second highest elongation rate after TRIP steel. For these reasons, it is mainly used in door outers, seat rails, seat belts, suspensions, arms, wheel discs, etc.
[0009] TRIP steel has a yield ratio in the range of 0.57 to 0.67 and is characterized by excellent formability (high ductility), making it suitable for parts that require high formability, such as members, roofs, seat belts, bumper rails, etc.
[0010] In addition to its low yield ratio, CP steel has high elongation and bending workability, making it suitable for use in side panels and under-body reinforcements, while FB steel has excellent hole expansion properties and is primarily used in suspension lower arms and wheel discs.
[0011] Among these, DP steel is mainly composed of ferrite with excellent ductility and hard phases (martensite and bainite phases) with high strength, and may contain a small amount of retained austenite. Such DP steel has low yield strength, high tensile strength, low yield ratio (YR), and excellent properties such as high work hardening rate, high ductility, continuous yield behavior, room temperature aging resistance, and bake hardenability. In addition, by controlling the fraction, degree of recrystallization, and distribution uniformity of each phase, it can be manufactured into high-strength steel with high bendability.
[0012] However, in order to secure ultra-high strength of tensile strength of 980 MPa or more, it is necessary to increase the fraction of hard phases such as martensite, which is advantageous for improving strength. However, in this case, the yield strength increases, which causes defects such as cracks during press forming.
[0013] Generally, DP steel for automobiles is manufactured by producing slabs through the steelmaking and continuous casting processes, and then the slabs are heated, roughly rolled, and finished hot rolled to obtain hot rolled coils, which are then annealed to produce the final product.
[0014] Here, the annealing process is a process that is mainly performed during the manufacture of cold-rolled steel sheets. Cold-rolled steel sheets are manufactured by removing surface scale by acid washing a hot-rolled coil, cold rolling at a certain rolling reduction at room temperature, and then passing through an annealing process and an additional temper rolling process as necessary.
[0015] Cold-rolled steel sheet (cold-rolled material) obtained by cold rolling is itself in a very hard state and is unsuitable for manufacturing parts that require workability. Therefore, in a subsequent process, it is softened by heat treatment in a continuous annealing furnace to improve workability.
[0016] As an example, the annealing process involves heating a steel sheet (cold-rolled material) to about 650 to 850°C in a heating furnace and then maintaining the temperature for a certain period of time, which reduces the hardness and improves workability through recrystallization and phase transformation.
[0017] Steel sheets that do not undergo an annealing process have high hardness, especially surface hardness, and lack workability, whereas steel sheets that have undergone an annealing process have a recrystallized structure that reduces hardness, yield point, and tensile strength, thereby enabling the improvement of workability.
[0018] A representative method for reducing the yield strength of DP steel is to completely recrystallize ferrite in the heating process during continuous annealing to produce it in the form of equiaxed grains, so that when austenite is generated and grown in the subsequent process, it will be in the form of equiaxed grains, and it is advantageous to form a uniform austenite phase with a small grain size.
[0019] On the other hand, as a conventional technique for improving the workability of high-strength steel, Patent Document 1 presents a method for refining the structure, specifically, a method for dispersing fine precipitated copper particles with a particle size of 1 to 100 nm inside the structure of a dual-phase steel sheet mainly composed of martensite phase. However, this technique requires the addition of 2 to 5% Cu to obtain good fine precipitated phase particles, which may cause red brittleness due to the large amount of Cu, and there is a problem that the manufacturing cost increases excessively.
[0020] Patent Document 2 discloses a steel sheet having a ferrite matrix and a structure containing 2 to 10 area % of pearlite, and having improved strength through precipitation strengthening and grain refinement by adding carbonitride-forming elements (e.g., Ex, Ti). While the above steel sheet is favorable in terms of hole expandability, there is a limit to further increasing the tensile strength, and the yield strength is high and the ductility is low, resulting in the problem of cracks occurring during press forming.
[0021] Patent Document 3 discloses a technology for producing a cold-rolled steel sheet that utilizes a tempered martensite phase to simultaneously obtain high strength and high ductility and has an excellent sheet shape after continuous annealing. However, since the carbon (C) content in the steel is high at 0.2% or more, there is a problem of poor weldability, as well as a problem of the occurrence of dent defects in the furnace due to the addition of a large amount of Si.
[0022] In view of the above-mentioned conventional techniques, in order to improve formability such as bendability of high strength steel that satisfies physical properties such as weldability, it is necessary to develop a method capable of lowering yield strength and improving ductility. [Prior art documents] [Patent documents]
[0023] [Patent Document 1] JP 2005-264176 A [Patent Document 2] Korean Patent Publication No. 2015-0073844 [Patent Document 3] JP 2010-090432 A Summary of the Invention [Problem to be solved by the invention]
[0024] One aspect of the present invention is to provide a high-strength steel plate that has a low yield ratio and high strength while having excellent formability such as bendability due to improved ductility, and is suitable as a material for automobile structural members, etc.; and a method for producing the same.
[0025] The object of the present invention is not limited to the above. The object of the present invention can be understood from the entire content of this specification, and a person having ordinary skill in the art to which the present invention belongs will have no difficulty in understanding further object of the present invention. [Means for solving the problem]
[0026] One embodiment of the present invention contains, by weight percent, carbon (C): 0.05 to 0.12%, manganese (Mn): 2.0 to 3.0%, silicon (Si): 0.5% or less (excluding 0%), chromium (Cr): 1.0% or less (excluding 0%), niobium (Nb): 0.1% or less (excluding 0%), titanium (Ti): 0.1% or less (excluding 0%), boron (B): 0.0025% or less (excluding 0%), aluminum (sol.Al): 0.02 to 0.05%, phosphorus (P): 0.05% or less (excluding 0%), sulfur (S): 0.01% or less (excluding 0%), nitrogen (N): 0.01% or less (excluding 0%), iron (Fe) and other inevitable impurities, The present invention provides a high-strength steel sheet having excellent bendability and formability, the microstructure of which includes ferrite with an area fraction of 35-50%, bainite with an area fraction of 35-45%, and the balance martensite, the ferrite consisting of unrecrystallized ferrite with an area fraction of 8-15% and recrystallized ferrite with an area fraction of 27-35%.
[0027] Another aspect of the present invention includes the steps of preparing a steel slab having the above-mentioned alloy composition; heating the steel slab in a temperature range of 1100 to 1300 ° C; hot rolling the heated steel slab to produce a hot rolled steel sheet; coiling the hot rolled steel sheet in a temperature range of 400 to 700 ° C; cooling the hot rolled steel sheet to room temperature after the coiling; cold rolling the cooled hot rolled steel sheet to produce a cold rolled steel sheet; continuous annealing the cold rolled steel sheet; performing primary cooling after the continuous annealing to a temperature range of 650 to 700 ° C at an average cooling rate of 1 to 10 ° C / s; and performing secondary cooling after the primary cooling to a temperature range of 300 to 580 ° C at an average cooling rate of 5 to 50 ° C / s, The present invention provides a method for producing a high-strength steel sheet having excellent bendability and formability, characterized in that the cold rolling is carried out in 7 passes or less and the total rolling reduction is 55 to 70%. Effect of the Invention
[0028] According to the present invention, it is possible to provide a steel sheet having high strength, excellent bendability (three-point bending property), and improved formability and impact resistance.
[0029] The steel sheet of the present invention, which has improved formability, can prevent processing defects such as cracks and wrinkles during press forming, and is therefore suitable for use in structural parts that require processing into complex shapes. Furthermore, it is also effective in producing materials with improved crash resistance so that defects such as cracks are less likely to occur when an automobile using such parts inevitably crashes. [Brief description of the drawings]
[0030] [Figure 1] 1 shows a microstructure photograph of an inventive steel according to an embodiment of the present invention. [Diagram 2] 1 shows a microstructure photograph of a comparative steel according to an embodiment of the present invention. [Diagram 3] 2 is a graph showing changes in physical properties depending on a reduction rate during cold rolling in one embodiment of the present invention. [Figure 4]1 is a graph showing changes in physical properties depending on annealing temperature in one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] The inventors of the present invention have conducted extensive research in order to develop a material having a level of formability suitable for use in automotive parts that require processing into complex shapes.
[0032] In particular, the inventors have confirmed that the target can be achieved by inducing sufficient recrystallization of the soft phase that affects the ductility of the steel, and have completed the present invention.
[0033] The present invention will be described in detail below.
[0034] A high-strength steel plate with excellent bendability and formability according to one embodiment of the present invention can contain, by weight percent, carbon (C): 0.05 to 0.12%, manganese (Mn): 2.0 to 3.0%, silicon (Si): 0.5% or less (excluding 0%), chromium (Cr): 1.0% or less (excluding 0%), niobium (Nb): 0.1% or less (excluding 0%), titanium (Ti): 0.1% or less (excluding 0%), boron (B): 0.0025% or less (excluding 0%), aluminum (sol.Al): 0.02 to 0.05%, phosphorus (P): 0.05% or less (excluding 0%), sulfur (S): 0.01% or less (excluding 0%), and nitrogen (N): 0.01% or less (excluding 0%).
[0035] The reasons for restricting the alloy composition of the steel plate provided in the present invention as described above will be described in detail below.
[0036] Meanwhile, unless otherwise specified in the present invention, the content of each element is based on weight, and the proportion of the structure is based on area.
[0037] Carbon (C): 0.05~0.12% Carbon (C) is an important element that is added for solid solution strengthening. Such C combines with precipitated elements to form fine precipitates, thereby contributing to improving the strength of steel.
[0038] If the C content exceeds 0.12%, the hardening ability increases and martensite is formed during cooling during steel manufacturing, resulting in an excessive increase in strength but a decrease in elongation. In addition, the weldability is poor, which may cause welding defects when processed into parts. On the other hand, if the C content is less than 0.05%, it becomes difficult to ensure the target level of strength.
[0039] Therefore, the C content may be 0.05 to 0.12%, more preferably 0.06% or more, and 0.10% or less.
[0040] Manganese (Mn): 2.0-3.0% Manganese (Mn) is an element that is advantageous in preventing hot embrittlement due to the formation of FeS by precipitating sulfur (S) in steel as MnS, and in strengthening the steel through solid solution.
[0041] If the Mn content is less than 2.0%, not only will the above-mentioned effects not be obtained, but it will also be difficult to ensure the target level of strength. On the other hand, if the Mn content exceeds 3.0%, there is a high possibility that problems such as weldability and hot rolling will occur, and at the same time, martensite will be more easily formed due to the increased hardenability, which may result in a decrease in ductility. In addition, there is a problem that Mn-Bands (Mn oxide bands) are excessively formed in the structure, increasing the risk of defects such as processing cracks. And there is a problem that Mn oxides dissolve onto the surface during annealing, greatly impairing platability.
[0042] Therefore, the Mn content can be 2.0 to 3.0%, and more advantageously 2.2 to 2.8%.
[0043] Silicon (Si): 0.5% or less (excluding 0%) Silicon (Si) is a ferrite stabilizing element that promotes ferrite transformation and is advantageous in ensuring the target level of ferrite fraction. It also has good solid solution strengthening ability and is effective in increasing the strength of ferrite, making it a useful element in ensuring strength without reducing the ductility of steel.
[0044] If the Si content exceeds 0.5%, the solid solution strengthening effect becomes excessive, which in turn reduces ductility and induces defects in the surface scale, adversely affecting the plating surface quality. Also, there is a problem of impairing the chemical conversion treatability.
[0045] Therefore, the Si content may be 0.5% or less, 0% may be excluded, and more preferably, 0.1% or more.
[0046] Chromium (Cr): 1.0% or less (excluding 0%) Chromium (Cr) is an element that facilitates the formation of the bainite phase and suppresses the formation of the martensite phase during annealing heat treatment, while forming fine carbides, thereby contributing to improved strength.
[0047] If the Cr content exceeds 1.0%, the bainite phase is excessively formed, which reduces the elongation, and if carbides are formed at the grain boundaries, the strength and elongation may be deteriorated. Also, there is a problem of an increase in manufacturing costs.
[0048] Therefore, the Cr content may be 1.0% or less, and 0% may be excluded.
[0049] Niobium (Nb): 0.1% or less (excluding 0%) Niobium (Nb) is an element that segregates at the austenite grain boundaries, suppresses the coarsening of austenite crystal grains during annealing heat treatment, and forms fine carbides, thereby contributing to improving strength.
[0050] If the Nb content exceeds 0.1%, coarse carbides precipitate, and the carbon content in the steel is reduced, resulting in poor strength and elongation, and an increase in manufacturing costs.
[0051] Therefore, the Nb content can be 0.1% or less, and 0% can be excluded.
[0052] Titanium (Ti): 0.1% or less (excluding 0%) Titanium (Ti) is an element that forms fine carbides, and contributes to ensuring yield strength and tensile strength. In addition, Ti precipitates N in steel as TiN and inhibits the formation of AlN from Al, which is inevitably present in steel, and therefore reduces the possibility of cracks occurring during continuous casting.
[0053] If the Ti content exceeds 0.1%, coarse carbides are precipitated, which reduces the carbon content in the steel, and this may result in a decrease in strength and elongation. In addition, there is a risk of nozzle clogging during continuous casting, which may increase the production cost.
[0054] Therefore, the Ti content may be 0.1% or less, and 0% may be excluded.
[0055] Boron (B): 0.0025% or less (excluding 0%) Boron (B) is an element that delays the transformation of austenite into pearlite during the cooling process after annealing heat treatment. However, if the B content exceeds 0.0025%, B will be excessively concentrated on the surface, which may cause deterioration of plating adhesion.
[0056] Therefore, the above B can be contained in an amount of 0.0025% or less, and 0% can be excluded.
[0057] Aluminum (sol.Al): 0.02~0.05% Aluminum (sol.Al) is an element added to steel for grain refinement and deoxidation, and if its content is less than 0.02%, aluminum-killed steel cannot be manufactured in a stable state. On the other hand, if its content exceeds 0.05%, it has the effect of refining crystal grains and improving strength, but excessive inclusions are formed during steelmaking continuous casting operations, increasing the risk of surface defects in plated steel sheets.
[0058] Therefore, the sol. Al content can be 0.02 to 0.05%.
[0059] Phosphorus (P): 0.05% or less (excluding 0%) Phosphorus (P) is a substitutional element with the greatest effect on solid solution strengthening, and is an element that is advantageous in improving in-plane anisotropy and ensuring strength without significantly reducing formability. However, if P is added in excess, the possibility of brittle fracture increases significantly, increasing the possibility of slab breakage during hot rolling, and impairing the plating surface properties.
[0060] Therefore, in the present invention, the P content can be controlled to 0.05% or less, and 0% can be excluded in consideration of the level of unavoidable addition.
[0061] Sulfur (S): 0.01% or less (excluding 0%) Sulfur (S) is an element that is inevitably added as an impurity element in steel, and since it impairs ductility, it is preferable to control its content as low as possible. In particular, since S has the problem of increasing the possibility of generating red shortness, it is preferable to control its content to 0.01% or less. However, 0% can be excluded in consideration of the level of S that is inevitably added during the manufacturing process.
[0062] Nitrogen (N): 0.01% or less (excluding 0%) Nitrogen (N) is a solid solution strengthening element, but if its content exceeds 0.01%, there is a high possibility that brittleness will occur and it may combine with Al in the steel to cause excessive precipitation of AlN, which may impair the quality of continuous casting.
[0063] Therefore, the N content may be 0.01% or less, and 0% may be excluded in consideration of the level of unavoidable addition.
[0064] The remaining component of the present invention is iron (Fe). However, in normal manufacturing processes, unintended impurities may be inevitably mixed in from raw materials or the surrounding environment, and it is not possible to exclude them. Since these impurities are known to anyone skilled in normal manufacturing processes, the contents of all of them are not specifically mentioned in this specification.
[0065] The steel sheet of the present invention having the above-mentioned alloy composition can be composed of ferrite and hard phases, bainite phase and martensite phase, as a microstructure.
[0066] Specifically, the steel sheet of the present invention may contain a ferrite phase with an area fraction of 35 to 50%, a bainite phase with an area fraction of 35 to 45%, and a martensite phase as the remainder, and may further contain a small amount of retained austenite phase.
[0067] The ferrite phase is composed of unrecrystallized ferrite and recrystallized ferrite, and the unrecrystallized ferrite may have an area fraction of 8 to 15%, and the recrystallized ferrite may have an area fraction of 27 to 35%.
[0068] The higher the degree of non-recrystallization of ferrite, the higher the heterogeneity in the structure, which may result in poor workability. Therefore, it is preferable to induce the formation of a homogeneous structure in the steel through appropriate recrystallization.
[0069] If the fraction of the unrecrystallized ferrite is less than 8%, recrystallization may proceed excessively, resulting in a deterioration in strength, whereas if the fraction exceeds 15%, the elongated hard phase is unevenly distributed within the structure, resulting in an excessively high yield strength and making it difficult to ensure workability.
[0070] If the proportion of the bainite phase is excessively high, the proportion of the soft phase will be relatively low, making it impossible to ensure the target level of formability. On the other hand, if the proportion of the soft phase is less than 35%, there is a risk of poor bendability.
[0071] Of the structures excluding the ferrite and bainite phases, the martensite phase is advantageously contained at an area fraction of 20% or less (excluding 0%) in order to ensure ultra-high strength of tensile strength of 980 MPa or more, although there is no specific limit to the fraction. If the martensite phase fraction exceeds 20%, ductility decreases, making it difficult to ensure the target level of workability.
[0072] On the other hand, it is advantageous for the fraction of the retained austenite phase to not exceed 3%, and even if it is 0%, there is no problem in ensuring the intended physical properties.
[0073] The steel sheet of the present invention having the above-mentioned microstructure has a thickness of 0.5 to 2.5 mm, a tensile strength of 980 MPa or more, a yield strength of 550 to 650 MPa, and an elongation (total elongation) of 12% or more, and can have high ductility properties in addition to high strength.
[0074] Furthermore, the above steel sheet has a three-point bending angle of 90 degrees or more, and thus can have excellent bendability.
[0075] Hereinafter, a method for producing a high strength steel plate excellent in bendability and formability according to another aspect of the present invention will be described in detail.
[0076] In brief, the present invention can produce the desired steel sheet through the steps of [steel slab heating - hot rolling - coiling - cold rolling - continuous annealing], and each step will be described in detail below.
[0077] [Heating steel slab] First, a steel slab satisfying the above-mentioned alloy composition can be prepared and then heated.
[0078] This step is performed to smoothly carry out the subsequent hot rolling step and to sufficiently obtain the desired physical properties of the steel sheet. In the present invention, the conditions of such a heating step are not particularly limited, and normal conditions may be used. As an example, the heating step can be performed in a temperature range of 1100 to 1300°C.
[0079] [Hot rolling] The steel slab heated as described above can be hot rolled to produce a hot rolled steel sheet, and finish hot rolling can be performed at an outlet side temperature of Ar3 or more and 1000°C or less.
[0080] If the exit temperature during the finish hot rolling is less than Ar3, the hot deformation resistance increases rapidly, the top, tail and edges of the hot rolled coil become single-phase regions, and the in-plane anisotropy increases, which may deteriorate the formability. On the other hand, if the temperature exceeds 1000°C, the rolling load decreases relatively, which is advantageous for productivity, but there is a risk of thick oxide scale being generated.
[0081] More specifically, the finish hot rolling can be carried out in the temperature range of 760 to 940°C.
[0082] [Winding] The hot-rolled steel sheet produced as described above can be wound into a coil.
[0083] The coiling can be performed at a temperature range of 400 to 700° C. If the coiling temperature is less than 400° C., martensite or bainite phase is excessively formed, resulting in an excessive increase in strength of the hot-rolled steel sheet, and problems such as defective shape due to the load during the subsequent cold rolling may occur. On the other hand, if the coiling temperature exceeds 700° C., there is a problem that surface scale increases and pickling properties deteriorate.
[0084] [cooling] The coiled hot-rolled steel sheet is preferably cooled to room temperature at an average cooling rate of 0.1° C. / s or less (excluding 0° C. / s). In this case, the coiled hot-rolled steel sheet may be cooled after being transported, stacked, etc., and the process before cooling is not limited thereto.
[0085] In this manner, by cooling the coiled hot-rolled steel sheet at a constant speed, it is possible to obtain a hot-rolled steel sheet in which carbides that serve as austenite nucleation sites are finely dispersed.
[0086] [Cold rolling] The hot-rolled steel sheet coiled as described above can be cold-rolled to produce a cold-rolled steel sheet.
[0087] The inventors of the present invention have confirmed that in the case of a multi-stand process using a general continuous rolling mill (ex, 5 or more roll stands) for manufacturing cold rolled steel sheets in the technical field of the present invention, there is no problem in rolling to a target thickness, but there is a limit in ensuring material uniformity and also in productivity. Therefore, the present invention has a feature of providing a method for manufacturing cold rolled steel sheets using an ultra-thin cold rolling mill (ZRM) as a method that can overcome the limitations of the above-mentioned cold rolling process. For example, the rolling mill may be a rolling mill having a pair of work rolls and a number of back rolls (ex, about 17 to 19) connected to the work rolls, and is not limited thereto as long as it can reach the rolling load.
[0088] Specifically, cold rolling using the ultra-thin cold rolling mill (ZRM) can be performed in 7 passes or less, preferably 5 to 7 passes, which is characterized by being performed in fewer passes than conventional continuous rolling mills (8 to 14 passes).
[0089] Furthermore, the present invention has an economically advantageous effect since the above-mentioned seven or less passes can be set in one stand and strong reduction can be achieved with a total reduction rate of 55% or more, preferably 55 to 70%.
[0090] If the total reduction rate during cold rolling is less than 55%, ferrite recrystallization is delayed, making it difficult to obtain a fine and uniform austenite phase.On the other hand, if the total reduction rate exceeds 70%, excessive recrystallization and fine grain formation may result in an excessive increase in yield strength, causing a decrease in workability, or excessive recrystallization and recovery may occur during annealing, suppressing phase transformation and making it difficult to form a low-temperature transformation phase, making it difficult to ensure a target level of strength.
[0091] In the present invention, the target thickness can be achieved with a small number of passes during cold rolling using the ultra-thin cold rolling mill, but in the case of thick materials with a hot-rolled steel sheet thickness of 4.0 mm or more, the target reduction can be achieved by repeating cold rolling 15 to 20 times (passes) using a reversing mill. In this case, 15 to 20 passes can be set for one stand. A reversing rolling mill is a type of rolling mill used for rolling thin materials, and refers to a rolling mill that rolls a material while reciprocating between a pair of rolls, and one way of the reciprocating movement of the material can be set to one pass.
[0092] As described above, the present invention has an effect of further improving the material uniformity of the produced cold-rolled steel sheet by performing cold rolling under strong reduction, and ensuring a thinner thickness compared to conventional cold-rolled steel sheets.
[0093] Preferably, the cold rolled steel sheet of the present invention has a thickness of 0.5 to 2.5 mm.
[0094] In the present invention, the hot-rolled steel sheet can be pickled before the cold rolling, and the pickling process can be carried out by a conventional method.
[0095] [Continuous annealing] The cold rolled steel sheet produced as described above is preferably subjected to a continuous annealing process. As an example, the continuous annealing process can be performed in a continuous annealing furnace (CAL).
[0096] Typically, a continuous annealing furnace (CAL) may be composed of a heating zone, a soaking zone, a cooling zone (slow cooling zone and quenching zone), and an overaging zone, if necessary. A cold-rolled steel sheet is charged into such a continuous annealing furnace, heated to a specific temperature in the heating zone, and after the target temperature is reached, the steel sheet is maintained for a certain period of time in the soaking zone.
[0097] In the present invention, the temperatures of the heating zone and the soaking zone can be controlled to be the same during the continuous annealing, which means that the end temperature of the heating zone and the start temperature of the soaking zone are controlled to be the same.
[0098] Specifically, the temperature of the heating zone and the soaking zone can be controlled to 770 to 810° C. If the temperature is less than 770° C., sufficient heat input for recrystallization cannot be applied, while if the temperature exceeds 810° C., the productivity decreases, and the austenite phase is excessively formed, so that the fraction of the hard phase after subsequent cooling increases significantly, which may deteriorate the ductility of the steel.
[0099] [Stepwise cooling] The cold-rolled steel sheet that has been continuously annealed as described above can be cooled to form a desired structure, and it is preferable to cool the steel sheet stepwise.
[0100] In the present invention, the stepwise cooling may be performed by primary cooling-secondary cooling. Specifically, after the continuous annealing, primary cooling may be performed at an average cooling rate of 1-10°C / s to a temperature range of 650-700°C, and then secondary cooling may be performed at an average cooling rate of 5-50°C / s to a temperature range of 300-580°C.
[0101] At this time, by carrying out the primary cooling more slowly than the secondary cooling, it is possible to suppress defects in the sheet shape that would otherwise occur due to a sudden drop in temperature during the secondary cooling, which is a relatively rapid cooling period.
[0102] If the end temperature of the first cooling is less than 650°C, the temperature is too low, resulting in low carbon diffusion activity and high carbon concentration in ferrite, while the carbon concentration in austenite is low, resulting in excessive hard phase fraction and high yield ratio, which increases the tendency for cracks to occur during processing. In addition, the cooling rates in the soaking zone and cooling zone (slow cooling zone) become too high, resulting in uneven sheet shape. If the end temperature exceeds 700°C, there is a disadvantage that an excessively high cooling rate is required for subsequent cooling (secondary cooling).
[0103] In addition, if the average cooling rate during the primary cooling exceeds 10°C / s, carbon diffusion cannot occur sufficiently. On the other hand, in consideration of productivity, the primary cooling step can be carried out at an average cooling rate of 1°C / s or more.
[0104] As described above, after the completion of the primary cooling, rapid cooling (secondary cooling) can be performed at a certain cooling rate or higher. If the secondary cooling end temperature is less than 300°C, cooling deviations may occur in the width and length directions of the steel plate, resulting in poor plate shape. On the other hand, if the temperature exceeds 580°C, the hard phase cannot be sufficiently secured, resulting in low strength.
[0105] Furthermore, if the average cooling rate during the secondary cooling is less than 5°C / s, the fraction of the hard phase may be excessive, whereas if it exceeds 50°C / s, the fraction of the hard phase may be insufficient.
[0106] On the other hand, if necessary, after the stepwise cooling is completed, an overaging treatment can be carried out.
[0107] The overaging treatment is a process of maintaining the temperature for a certain period of time after the secondary cooling end temperature, and since uniform heat treatment is performed in the width and length directions of the coil, it has the effect of improving the shape quality. For this reason, the overaging treatment can be performed for 200 to 800 seconds.
[0108] The overaging treatment can be carried out immediately after the completion of the secondary cooling, and therefore the temperature can be the same as the secondary cooling completion temperature or within the secondary cooling completion temperature range.
[0109] The high strength steel sheet according to the present invention manufactured as described above has a microstructure composed of a hard phase and a soft phase, and by maximizing ferrite recrystallization through an optimized cold rolling and annealing process, the steel sheet may have a structure in which hard phases, bainite and martensite, are uniformly distributed in the final recrystallized ferrite matrix.
[0110] As a result, the steel sheet of the present invention has a high strength of tensile strength of 980 MPa or more, while also ensuring a low yield ratio and high ductility, thereby ensuring good bendability and formability.
[0111] The present invention will be described in more detail with reference to the following examples. However, it should be noted that the following examples are intended to illustrate and explain the present invention in more detail, and are not intended to limit the scope of the present invention. The scope of the present invention is determined by the matters described in the claims and matters that can be reasonably inferred from the claims. EXAMPLES
[0112] (Example) After producing steel slabs having the alloy composition shown in Table 1 below, each steel slab was heated at 1200°C for 1 hour and then finish hot-rolled at a finish rolling temperature of 880 to 920°C to produce hot-rolled steel sheets. At this time, the thickness of each hot-rolled steel sheet was 2.1 to 3.5 mm, and in the case of steel with a cold-rolled material thickness of 0.8 mm (see Table 2), the thickness of the hot-rolled steel sheet was 8 mm.
[0113] Then, each hot-rolled steel sheet was coiled at 650°C and cooled to room temperature at a cooling rate of 0.1°C / s. Then, the coiled hot-rolled steel sheet was cold-rolled and continuously annealed under the conditions shown in Table 2 below, and then subjected to stepwise cooling (1st-2nd) and overaging treatment at 360°C for 520 seconds to produce the final steel sheet.
[0114] In this stepwise cooling, the first cooling was performed at an average cooling rate of 3°C / s, and the second cooling was performed at an average cooling rate of 20°C / s.
[0115] For each of the steel sheets produced as described above, the microstructure was observed and the tensile and processing properties were evaluated, and the results are shown in Table 3 below.
[0116] In this case, the tensile test for each test piece was carried out by taking a JIS No. 5 size tensile test piece in the direction perpendicular to the rolling direction and then carrying out the tensile test at a strain rate of 0.01 / s.
[0117] On the other hand, the three-point bending test for evaluating the bendability was performed based on the VDA standard (VDA238-100) specified by the German Association of the Automotive Industry, and the bending angle was measured by converting the displacement at the maximum load measured in the bending test to an angle based on the VDA standard. The dimensions of the test piece were 60mm x 60mm, the diameter of the bending roll was 30mm, the distance between the rolls was 2.9mm, the punch R value was 0.4mm, and the punch pressing speed was 20mm / min.
[0118] Among the structural phases, the bainite and martensite phases, which are hard phases, were observed by SEM at 5000x magnification after nital etching. The fraction of the observed hard phases was measured. The fraction of each of the other phases was also measured using SEM and an image analyzer after nital etching. At this time, the non-recrystallized ferrite was expressed as the fraction of ferrite with deformed structure remaining from the total ferrite fraction through the image analyzer.
[0119] In addition, to check whether the weldability standards are met after processing of the automobile structure, the carbon equivalent (C eq ) values were measured and calculated according to the following formula. Formula (1)...C eq(%) = C + (Si / 30) + (Mn / 20) + 2P + 4S (where each element represents its weight content (%).)
[0120] [Table 1]
[0121] [Table 2]
[0122] [Table 3]
[0123] As shown in Tables 1 to 3 above, in Examples 1 to 6, in which the steel alloy composition and manufacturing conditions, particularly the cold rolling and continuous annealing processes, all satisfy the points proposed by the present invention, sufficient ferrite recrystallization is carried out during the annealing treatment process after cold rolling, and thus the steel has high strength and yield strength that is advantageous for sheet processing, as well as excellent elongation and three-point bending properties, which confirms that it is possible to ensure the target level of formability.
[0124] In particular, the above-mentioned examples of the invention are characterized by improved uniformity of the material properties of the steel sheet, as the fraction of recrystallized ferrite is 27% or more. Steel recrystallization is a phenomenon in which ferrite atoms are rearranged during annealing, and the higher the degree of recrystallization, the more austenite transformation occurs in various directions, which increases the overall uniformity of the material properties of the steel, which is advantageous for improving workability.
[0125] On the other hand, in Comparative Examples 1 and 2, in which the soaking temperature during continuous annealing in the steel sheet manufacturing process is low and the cold reduction is low, the ferrite phase that is not sufficiently recrystallized is excessive, the yield strength and tensile strength are excessively high, and the elongation and three-point bending angle are low, resulting in deteriorated workability. Also, in Comparative Example 3, the soaking temperature during continuous annealing is low and the cold reduction is low, so that the non-recrystallized ferrite phase is excessively formed, resulting in deteriorated three-point bending angle.
[0126] In Comparative Examples 6, 7, and 11 to 13, the annealing temperature for driving recrystallization met the requirements of the present invention, but the total reduction rate during cold rolling was controlled to less than 55%, which led to the development of elongated hard phases, resulting in excessively high yield strength and tensile strength, and thus poor workability.
[0127] Comparative Example 8 also had a total reduction rate during cold rolling of less than 55%, but the reduction rate was higher than those of Comparative Examples 6 and 7, and the workability was at the level of the present invention, but the ductility was degraded.
[0128] In Comparative Examples 4 to 5, 9 to 10, and 14 to 15, the total reduction rate during cold rolling was 90%, which was extremely excessive.
[0129] Among these, Comparative Examples 4 to 5 and 10 are cases in which recrystallization proceeded excessively during annealing after cold rolling, suppressing the reverse transformation of austenite, resulting in deterioration of strength. Since the reverse transformation of austenite does not occur much in recrystallized ferrite, the reverse transformation of austenite may be suppressed in an environment where the driving force for recrystallization is very high, resulting in a decrease in the fraction of martensite during cooling or an increase in the fraction of ferrite in the final structure.
[0130] In Comparative Example 9, the yield strength was excessively high due to the effect of grain refinement caused by an excessive rolling reduction, making forming difficult and resulting in an increased processing ratio.
[0131] In Comparative Examples 14 and 15, the austenite was excessively formed during the annealing process due to the strong rolling and the relatively high annealing temperature, and the hard phase fraction was also high during cooling, resulting in an excess yield strength.
[0132] FIG. 1 shows microstructure photographs of Inventive Examples 3 and 4, and FIG. 2 shows microstructure photographs of Comparative Examples 6 and 7.
[0133] As shown in FIG. 1, it can be seen that the steel sheet according to the present invention has a sufficient fraction of recrystallized ferrite matrix, and a homogeneous and fine bainite phase and a certain fraction of martensite phase are formed.
[0134] On the other hand, as shown in Fig. 2, in Comparative Examples 6 and 7, it can be seen that ferrite was elongated in the rolling direction, and bainite was formed in the same form due to insufficient recrystallization. It can be seen that the high proportion of bainite resulted in excessively high yield strength and yield ratio, resulting in poor formability.
[0135] FIG. 3 is a graph showing the change in workability due to the reduction ratio during cold rolling, and FIG. 4 is a graph showing the change in workability due to the annealing temperature.
[0136] As shown in FIG. 3, under the annealing conditions proposed in the present invention, when the reduction rate during cold rolling is 55% or more, it is possible to simultaneously satisfy the elongation rate and the three-point bending angle.
[0137] On the other hand, when a rolling reduction of 45% or more is applied during cold rolling, it is possible to improve the elongation and three-point bending angle. However, in order to ensure the workability targeted in the present invention, it is necessary to control the alloy composition and annealing conditions to control phase transformation and recrystallization (Figure 4).
Claims
1. In weight percent, it contains carbon (C): 0.05 to 0.12%, manganese (Mn): 2.0 to 3.0%, silicon (Si): 0.5% or less (excluding 0%), chromium (Cr): 1.0% or less (excluding 0%), niobium (Nb): 0.1% or less (excluding 0%), titanium (Ti): 0.1% or less (excluding 0%), boron (B): 0.0025% or less (excluding 0%), aluminum (sol. Al): 0.02 to 0.05%, phosphorus (P): 0.05% or less (excluding 0%), sulfur (S): 0.01% or less (excluding 0%), and nitrogen (N): 0.01% or less (excluding 0%), and is composed of iron (Fe) and other unavoidable impurities, A high-strength steel plate having excellent bendability and formability, the microstructure of which includes ferrite having an area fraction of 35 to 50%, bainite having an area fraction of 35 to 45%, and the remainder martensite, the ferrite including unrecrystallized ferrite having an area fraction of 8 to 15% and recrystallized ferrite having an area fraction of 27 to 35%.
2. 2. The high strength steel plate having excellent bendability and formability according to claim 1, wherein the steel plate contains a martensite phase at an area fraction of 20% or less (excluding 0%).
3. The high strength steel plate having excellent bendability and formability according to claim 1, further comprising a retained austenite phase at an area fraction of 3% or less (including 0%).
4. The high-strength steel plate having excellent bendability and formability according to claim 1, wherein the steel plate has a tensile strength of 980 MPa or more, a yield strength of 550 to 650 MPa, and a total elongation of 12% or more.
5. 2. The high strength steel plate having excellent bendability and formability according to claim 1, wherein the steel plate has a three-point bending angle of 90 degrees or more.
6. The high strength steel plate having excellent bendability and formability according to claim 1, wherein the steel plate has a thickness of 0.5 to 2.5 mm.
7. preparing a steel slab containing, by weight percent, 0.05-0.12% carbon (C), 2.0-3.0% manganese (Mn), 0.5% or less (except 0%) silicon (Si), 1.0% or less (except 0%) chromium (Cr), 0.1% or less (except 0%) niobium (Nb), 0.1% or less (except 0%) titanium (Ti), 0.1% or less (except 0%) boron (B), 0.0025% or less (except 0%) aluminum (sol.Al), 0.02-0.05% phosphorus (P), 0.01% or less (except 0%) sulfur (S), and 0.01% or less (except 0%) nitrogen (N), as well as iron (Fe) and other unavoidable impurities; heating the steel slab to a temperature range of 1100-1300°C; hot rolling the heated steel slab to produce a hot rolled steel sheet; coiling the hot-rolled steel sheet at a temperature in the range of 400 to 700°C; cooling the hot-rolled steel sheet to room temperature after the coiling; cold rolling the cooled hot-rolled steel sheet to produce a cold-rolled steel sheet; subjecting the cold-rolled steel sheet to continuous annealing; After the continuous annealing, a primary cooling step is performed to a temperature range of 650 to 700° C. at an average cooling rate of 1 to 10° C. / s; and After the primary cooling, secondary cooling is performed at an average cooling rate of 5 to 50 ° C. / s to a temperature range of 300 to 580 ° C., The method for producing a high strength steel plate having excellent bendability and formability according to any one of claims 1 to 6, wherein the cold rolling is performed 7 passes or less, and a total rolling reduction is 55 to 70%.
8. The method for producing a high strength steel plate having excellent bendability and formability according to claim 7, wherein the hot rolling is finish hot rolling at an outlet side temperature of Ar3 or more and 1000°C or less.
9. The method for producing a high strength steel plate excellent in bendability and formability according to claim 7, wherein the cooling after the coiling is performed at a cooling rate of 0.1°C / s or less (excluding 0°C / s).
10. The method for producing a high strength steel plate having excellent bendability and formability according to claim 7, wherein the continuous annealing is performed in a facility equipped with a heating zone, a soaking zone, and a cooling zone, and the heating zone and the soaking zone are controlled to a temperature range of 770 to 810 ° C.
11. The method further includes a step of overaging after the secondary cooling, The method for producing a high strength steel plate having excellent bendability and formability according to claim 7, wherein the overaging treatment is carried out for 200 to 800 seconds.
Citation Information
Patent Citations
High-strength steel sheet having excellent impact properties and formability and method for manufacturing same
EP3730635A1
High-strength steel having adequate workability and manufacturing method therefor
JP2005264176A
High-strength cold-rolled steel sheet having excellent formability for extension flange, hot-dip galvanized steel sheet having the same formability, and method for manufacturing those
JP2007009317A
Super high-strength cold-rolled steel sheet excellent in ductility, and producing method of the same
JP2010090432A
KR2015-0073844